Comparative Study of Carbon Tax Regulations in Indonesia and Singapore - Wathan, Bilqis Alifia; Lie, Gunardi (Riwayat: Educational Journal of History and Humanities, 2025)
Climate change has become a global issue that urges countries to take concrete steps to reduce carbon emissions. Carbon tax is seen as a strategic fiscal instrument to achieve low-emission development. This study aims to compare the legal frameworks and carbon tax policies in Singapore and Indonesia, while assessing their implementation within the context of fiscal justice and environmental law. This research use normative juridical comparative approach, which analyze laws and regulations. The study findings indicate that Singapore implements a fixed rate carbon tax based on emission threshold alongside mandatory emissions reporting. Whilst Indonesia has only just begun implementing carbon tax with a minimum rate that is deemed too low as well as the lack of adequate technical regulations. Substantively, Indonesia still faces obstacles in determining the allocation of revenue from the carbon tax and ensuring the effectiveness of tax rates to influence economic behavior. This study concludes to emphasize the need for reformulation of carbon tax policy in Indonesia by adopting the polluter pays principle, implementing a mandatory emissions reporting system, and strengthening derivative regulations to be more adaptive and responsive to the challenges of climate change. Singapore's experience can serve as an important reference in designing a fairer and more effective carbon tax policy in Indonesia